Immune Thrombocytopenic Purpura Evolving into Hodgkin’s Disease in a Young Boy - Karimulla Mondal; Somnath Dasgupta; Kirtiman Mandal; Soumitra Ghosh; Nandini Chatterjee (Bengal Physician Journal)
Immune thrombocytopenic purpura (ITP) is a common bleeding disorder, and it may be primary (no potential etiologies found) or secondary (underlying associated conditions). The association between ITP and Hodgkin disease (HD) is well recognized in literature. ITP may occur before, during concurrent, and after the diagnosis of HD. Here we report a case of 15-year-old young boy, diagnosed as having ITP, who presented with persistent fever for a period of around 6 months and pancytopenia, and subsequently, we diagnosed HD. He responded well after chemotherapy.